Methodological Tools for the Assessment of Ecological and Socio-Economic Environment in the Region within the Limits of the Sustainability of Biosphere - Aleksey Yuryevich Davankov; Dmitry Yuryevich Dvinin; Yevgeniy Anatolyevich Postnikov (Экономика региона, 2016)
The article is devoted to the study of ecological and socio-economic environment as well as the development of effective methodological tool for the assessment of its stability. This tool allows to ascertain the level of economic activity of the regions within the limits of the sustainability of biosphere. In the article, the regional system is considered as the total of industrial enterprises, social infrastructure and natural environment creating a specific territorial ecological and socio-economic environment, whose stability depends on the level of economic activity measured by the capacity of territorial ecosystem. The use of a technique for the comparative assessment of the energy indicators of economic activity creating a specific ecological and socio-economic environment of the region as well as of the indicator of the ecological capacity of the territory is proved. The ecological capacity of the territory enables to better estimate the level of the sustainability of the region within the limits of sustainability of biosphere. This method allows to forecast the development of the studied territory by the measurement of general energy flow on the basis of closed material and energy flows. The research revealed an indicator of the sustainability of ecological and socio-economic environment of Ural Federal District. Yamalo-Nenets Autonomous District is the most stable, the Chelyabinsk region is the least stable, which is associated with both natural conditions and the specificities of economic structure. The labour productivity indicator, expressed in energy units, has revealed regions with rich natural resources. It was found that in these regions, there are significant material flows in the electricity industry that leads to a large proportion of greenhouse gas emissions. The assessment of the demographic capacity fully correlates with the calculations of the stability indicator of the regional system and the analysis of labour productivity in the region. In the future, these methodological tools will allow to develop a model of the management of a sustainable ecological and socio-economic environment of the region, taking into account the environmental capacity of biosphere